HOPE it helps!!!!!!!
plz mark as a brainliest answer!!!!!
Sqrt(1-3x)=x+3
[sqrt(1-3x)]^2=(x+3)^2
1-3x=(x+3)(x+3)
1-3x=x^2+6x+9
-3x=x^2+6x+8
0=x^2+9x+8
The answers are -1 and -8 BUT, we have to plug them back into the original equation to make sure we don't get a negative under the square root sign.
After doing this, we realize that only -1 works, so the answer is x=-1
Sorry that this took forever to answer. I was thinking of a good way to explain this, and if you need any further explanation, message me:)
Best wishes:)
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
Below are the answers:
<span>7. C. H(n) = ½n^2 + n + 1
</span>8. D. As the number of rows increases, the hexagonal rig gets closer to having twice as many lights as the square rig.
If the triangles are similar, then the corresponding ratio of their sides have equal ratios. Through ratio and proportion, we would determine the answer.
5/6 = x/9, where x is the length for side PN
Transposing the equation so that x is on the left side:
x = (5/6)*9
x = 7.5